Efecto de microorganismos, ácidos húmicos y fúlvicos en el crecimiento de plántulas de cacao (Theobroma Cacao L). - Castro Carrera, Jander Lizandro (2025)
This study was conducted in the nursery of the Agricultural Engineering program at the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, located in Bolívar Canton, Manabí Province, Ecuador. The objective of the research was to evaluate the effect of combining microorganisms with humic and fulvic acids, as biostimulants, on the agronomic performance and growth rate of cacao (Theobroma Cacao L.) seedlings of the CCN-51 variety at the nursery stage. The treatments evaluated were Trichoderma spp. (T1), Bacillus subtilis (T2), Humic and Fulvic Acids (T3), T spp. + HFA (T4), BS + HFA (T5), T spp. + HFA (T6), T spp. + BS + HFA (T7), and control treatment (T8). A completely randomized design was used, with eight treatments, three replications, and 24 experimental units. The evaluated variables were agronomic and daily growth parameters. Data were analyzed using analysis of variance and Tukey’s test (α = 0.05). The treatments did not significantly affect (p > 0.05) the recorded variables; however, most treatments numerically outperformed the control. It is concluded that, although the tested biostimulants did not achieve a statistically significant effect, they tend to promote better growth rates and agronomic performance in seedlings, making their use promising and worthy of continued study.